Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/jp9018662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Salt on the Excited-State Dynamics of Malachite Green in Bulk Aqueous Solutions and at Air/Water Interfaces: a Femtosecond Transient Absorption and Surface Second Harmonic Generation Study

Abstract: The ultrafast excited-state dynamics of Malachite Green (MG) in bulk aqueous solutions and at air/water interfaces, in particular the effect of the presence of various sodium salts in the aqueous phase, has been investigated by transient absorption and surface second harmonic generation. In bulk solutions, a slowing down of the ground-state recovery that can be unambiguously ascribed to the formation of aggregates of various sizes is observed at high (>0.3 M) salt concentrations only, with the exception of NaS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(87 citation statements)
references
References 66 publications
(136 reference statements)
9
78
0
Order By: Relevance
“…Although in our previous work, 24 we suggested that some features of the DADS found in transient absorption spectra of MG are consistent with S x being a vibrationally hot ground state, we believe that the arguments based on the current results prevail.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…Although in our previous work, 24 we suggested that some features of the DADS found in transient absorption spectra of MG are consistent with S x being a vibrationally hot ground state, we believe that the arguments based on the current results prevail.…”
Section: Resultssupporting
confidence: 54%
“…In previous studies, both single 21 and biexponential 24,26,48 decays of the SSHG signal have been observed with MG at various interfaces. The faster component is always identified with the decay of the S 1 state of monomeric MG molecules.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations